"We are of one blood": Hungarian popular music, nationalism and the trajectory of the song "Nélküled" through radicalization, folklorization and consecration. (4th May 2022) - Barna, Emília; Patakfalvi-Czirják, Ágnes
ABSTRACT: This paper addresses the relationship between popular music, nationalism and political power in a local context through the case of Hungary. Through the combination of musicological group analysis, fieldwork, interviews and media analysis, we follow the trajectory of the song "Nélküled" (Ismerős Arcok 2007 ) between 2007 and 2021 through its changing musical, social, media and political contexts. We identify three processes: firstly, the radicalization of the band in a subcultural context parallel to the development of the so-called national rock genre; secondly, the popularization and folklorization of the song, whereby it becomes at least partly detached from the original performing artists and embedded into the everyday culture of broader population segments; and finally, the parallel processes of political legitimation and cultural consecration. Our enquiry contributes a political economic perspective to the relatively under-theorized system of relationships between popular music, its social-cultural (genre, taste) and industrial logics, politics and the media by complementing media-based theories of subculture and mainstream with an understanding of political actors and processes. Through this, we also complement studies of everyday nationalism with viewing cultural practices in the political context of hegemonic right-wing ideology and increasing government control of the cultural and media industries.